Stockport Messenger dispute, 1983 (London, 1983)
1983 1980-95 "Stockport Messenger dispute, 1983" [BW0028], 1983, Trades Union Congress The National Graphical Association strike at the Stockport Messenger newspaper group, owned by Eddie Shah, related to the company breaking the closed shop agreement established across the provincial newspaper industry. In July 1983, six NGA members took strike action and were dismissed. The company successfully used the 1980 and 1982 Employment Acts to prevent both the boycotting of work and advertising, and secondary picketing at its other plants at Bury and Warrington. When the NGA ignored court injunctions, it faced heavy fines and sequestration of funds. There was a strike by NGA members on the national press in late November, but by January 1984, the union, with its funds frozen was having difficulty in continuing normal operations. It decided to purge its contempt and abide by the injunctions. The strike finally ended in May 1984 and the sacked workers were found work elsewhere. This photo shows Tony Dubbins, NGA General Secretary (centre front) with the 'Stockport Six' in December 1983